The effect of convalescent plasma therapy on the rate of nucleic acid negative conversion in patients with persistent COVID-19 test positivity - Wang, Yixuan; Xu, Zhe; Xu, Xue; Yang, Shuwen; Li, Yuanyuan; Zhang, Hanwen; Zhang, Yufeng; Wang, Fu-Sheng; Wang, Ying; Bi, Jingfeng (Frontiers in Pharmacology, 2024)
Objective: This study investigates the association between convalescent plasma therapy and the negative conversion rate in patients with persistent COVID-19 test positivity. Method: A retrospective analysis was conducted on patients with severe or mild to moderate COVID-19 whose viral nucleic acid tests remained positive for over 30 days. Patients were categorized into two groups: those who administered convalescent plasma therapy and those who were not. Data collected included information on therapy strategies used (convalescent plasma, corticosteroids, interferons, etc.), patients' demographic characteristics, comorbidities, therapeutic medications, and nucleic acid testing results. Patients in the convalescent plasma therapy group were matched 1:2 ratio with those in the non-convalescent plasma therapy group. Cumulative negative conversion rates on the fifth, tenth, and fifteenth days post-therapy initiation were analyzed as dependent variables. Independent variables included therapy strategies, demographic characteristics, comorbidities, and therapeutic medication usage. Univariate analysis was conducted, and factors with a pvalue (P) less than 0.2 were included in a paired Cox proportional hazards model.There was no statistically significant difference in the cumulative negative conversion rate between the convalescent plasma therapy group and the nonconvalescent plasma therapy group on the fifth, tenth, and fifteenth days. Specifically, on day the fifth, the negative conversion rate was 41.46% in the convalescent plasma therapy group compared to 34.15% in the non-convalescent plasma therapy group (HR:1.72, 95%CI: 0.82~3.61, P=0.15). On the tenth day, it was 63.41% in the convalescent plasma therapy group and 63.41% in the non-convalescent plasma therapy group (HR:1.25, 95%CI: 0.69~2.26, P=0.46). On the fifteenth day, the negative conversion rate was 85.37% in the convalescent plasma therapy group and 75.61% in the nonconvalescent plasma therapy group (HR: 1.19, 95%CI: 0.71~1.97, P=0.51).Our finding does not support the hypothesis that convalescent plasma therapy could accelerate the time to negative conversion in patients who consistently test positive for COVID-19.